“This land was Mexican once/ Was Indian always/ and is./ And will be again”. El papel de la memoria colectiva en la formación del discurso feminista chicano - Skonecka, Anna (Studia Romanica Posnaniensia, 2017)
The purpose of this article is to analyze the theoretical discourse of the Chicano feminists in order to determine the role of the collective memory in forming that discourse. The subject of the analysis will be mainly the mandatory reference to the postcolonial feminisms, namely the masterpiece by Gloria Anzaldúa and Cherríe Moraga titled Esta puente mi espalda. Voces de mujeres tercermundistas en los Estados Unidos. However, in order to present a complete overview of the Chicano discourse, we will also mention the work of scholars like Sonia Saldívar-Hull, Ana Castillo and Emma Pérez.